2019
DOI: 10.1002/jocb.420
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Tactical Innovation in Terrorist Attacks

Abstract: Terrorism provides a unique context for examining innovation, as the generation of novel, effective, and complex ideas are essential for survival in destructive and malevolent groups. Despite this, innovation remains an underdeveloped concept in terrorism research, at least from the creativity scholars. One reason for this is the limited empirical data about this phenomenon, making it unclear which tenets of creativity research hold versus which do not translate in the domain of terrorism. This two-part study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
(81 reference statements)
0
13
0
1
Order By: Relevance
“…As research on this topic has grown, the malevolent creativity framework has been used to understand deviant behaviors such as lying and cheating (e.g., Beaussart et al, 2013; Kapoor, 2015); counterproductive workplace behaviors (Harris, 2017); and criminal offending (Cropley & Cropley, 2011; Eisenman, 2008). Malevolent creativity has also been used as a framework to systematically investigate the successes and failures of terrorist innovations (Ackerman, 2016; Cropley et al, 2008; Dolnik, 2007; Gill, 2017; Gill et al, 2013; Knight et al, 2017; Ligon et al, 2015; Logan et al, 2020). For example, terrorist organizations innovate by developing new methods of engaging in violence.…”
Section: Malevolent Creativity and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…As research on this topic has grown, the malevolent creativity framework has been used to understand deviant behaviors such as lying and cheating (e.g., Beaussart et al, 2013; Kapoor, 2015); counterproductive workplace behaviors (Harris, 2017); and criminal offending (Cropley & Cropley, 2011; Eisenman, 2008). Malevolent creativity has also been used as a framework to systematically investigate the successes and failures of terrorist innovations (Ackerman, 2016; Cropley et al, 2008; Dolnik, 2007; Gill, 2017; Gill et al, 2013; Knight et al, 2017; Ligon et al, 2015; Logan et al, 2020). For example, terrorist organizations innovate by developing new methods of engaging in violence.…”
Section: Malevolent Creativity and Innovationmentioning
confidence: 99%
“…In particular, the development of car bombs using fertilizer-based explosives was a novel and effective method of violence adopted by the IRA. More recently, Logan et al (2020) examined the underlying dimensions of innovative products in a large corpus of terrorist attacks. The authors found that the three dimensions of innovative products (e.g., Besemer & O'Quinn, 1999) also manifest in terrorist attacks: novelty, relevance, and elegance.…”
Section: Malevolent Creativity and Innovationmentioning
confidence: 99%
“…CULTURALLY CONSTRUCTED CREATIVITY Researchers find differences in the ways that cultures define and recognize creativity (C ßelik and Lubart, 2016;Logan et al, 2019;Lubart, 2010;Morris & Leung, 2010;Weisberg, 2015;Yue et al, 2011). For example, Leung et al (2004) found that in empirical research, Western students performed better on creativity assessments than Asians.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…First of all, the scope of terrorists’ actions is not geographically limited, any facility can be attacked or blown up almost anywhere in the country (Haimes, 2004). Second, the methods used to carry out a terrorist attack and the possible objects of attack are extremely numerous (Logan et al , 2019). Third, the maximum damage from a terrorist attack cannot be accurately predicted (Ezell et al , 2010).…”
Section: Introductionmentioning
confidence: 99%